INTEGRATION OF PROBLEM-BASED LEARNING AND NUMBER MONOPOLY: STRATEGIES FOR IMPROVING ELEMENTARY SCHOOL STUDENTS' MATHEMATICAL LITERACY - Agung Nugroho; Yolanda Oktaufika; Anggun Pria Wibowo (JURNAL EDUSCIENCE, 2026)
Purpose – Mathematical literacy is an essential competency for every student as it plays a vital role in understanding and solving mathematical problems. However, in practice, this ability remains relatively low among elementary school students. This study aims to investigate improvements in mathematical literacy among second-grade students through the implementation of the Problem-Based Learning (PBL) model, supported by the Monopoly Number Game as a learning medium.Methodology – The research employed a Classroom Action Research (CAR) design, conducted in two cycles, with 21 second-grade students of SD Negeri 3 Bancarkembar as the participants. Data were collected through tests and observations to assess students' development of mathematical literacy.Findings – The findings reveal a significant improvement after applying PBL with the monopoly game. The Percentage of students' mathematical literacy increased from 33.33% in the pre-cycle to 57.14% in the first cycle and reached 85.71% in the second cycle. These results demonstrate that integrating the PBL model with an engaging game-based medium can foster meaningful, enjoyable, and effective learning, ultimately enhancing elementary school students' mathematical literacy.Contribution – The study's findings suggest that an innovative integration of PBL and educational games can be an alternative strategy to improve students' literacy skills in mathematics at the primary school level.